GENETIC ALGORITHM GA TO OPTIMIZEMACHINING PARAMETERS INTURNING OPERATION: A REVIEW - Nizam, M.A.R., Mohamad, B.M.,Adnan, J.A., (Journal of Advanced Manufacturing Technology (JAMT), 2014)
The determination of optimal cutting parameters have significant importance for economic machining in minimizing of particularoperating mistakes like tool fraction,wear,and chatter. The evolutionary algorithm GA is used to improve many solutions of optimization complex problems in many applications. This paper reviewed the ideal selection of cutting parameters in turning operation using GA and its variants. This study deals with GA algorithm in different machining aspects in turning operation like surface roughness, production rate, tool life, production cost, machining time and cuttingtemperature. The survey showed that there aremany papers in the field of turning parameters optimization using GA, but there is a lack in studies in the field of cutting temperature optimization in turning operation which is very important problem in machining operation.In addition, there arerare papers that studied dry turning operations.